Genome-Wide Identification, Characterization and Expression Analyses of Heat Shock Protein-Related Genes in a Highly Invasive Ascidian Ciona savignyi - Huang, Xuena; Li, Shiguo; Gao, Yangchun; Zhan, Aibin (Frontiers in Physiology, 2018)
Biological response to rapid changing environments is an outstanding research question in ecology and evolution. Biological invasions provide excellent “natural” experiments to study such a complex response process, as invaders often encounter rapidly changing environments during biological invasions. The regulation of heat shock proteins (Hsp) is a common pathway responsible for various environmental stresses; however, the comprehensive study on Hsp system across the whole genome and potential roles in determining invasion success are still largely unexplored. Here we used a marine invasive model ascidian, Ciona savignyi, to investigate transcriptional response of heat shock protein-related genes to harsh environments. We identified 31 genes, including three Hsp20, six Hsp40, 10 Hsp60, seven Hsp70, three Hsp90, one Hsp100 and one heat shock transcription factor (Hsf), acorss the whole genome of Ciona savignyi. We characterized gene structure and protein motifs, and identified potential heat shock elements (HSE) in promoters of Hsp genes. The expression analysis showed that most Hsp genes, but not all, were involved in transcriptional response to temperature and salinity changes in a time and stress-specific pattern, and the maximum amplitude of induction occurred in Hsp70-4 after 1-hour of high temperature treatment. However, the Hsf gene was scarcely induced and limited interactions were predicted between Hsp and Hsf genes. Our study provide the first systematic genome-wide analysis of Hsp and Hsf family in the marine invasive model ascidian, and Our results are expected to dissect heat shock protein-based molecular mechanisms responsible for extreme environmental adaptation using Ciona as a model system.